V. I. Lenin on Democracy. Issue 4 (1st October 2020) - Pateman, Joe
ABSTRACT: The concept of democracy has a prominent place in the ideological legacy of V. I. Lenin, the founder of the Communist Party of the Soviet Union and the leader of the world's first socialist state. In opposition to the Marxist revisionists of his era, who defined democracy as a "pure" category, a "neutral" form of government, Lenin highlighted its class essence. Democracy for him expresses the rule of a definite class. From this proposition he derived the following theses: First, democracy is a political means of class struggle, and it cannot resolve this struggle. Second, democracy for one class means dictatorship for another. Third, democracy precludes freedom. It cannot "free" everyone. These claims have had a lasting impact upon the theory and practice of Marxism. They have also been routinely misunderstood and unfairly criticised. Lenin provides several insights into the contradictions of democracy. They remain relevant for democratic struggles today.